Association between female genital mutilation/cutting and caesarean delivery in singleton births across Sub-Saharan Africa - Demisu Zenbaba; Sylvester Okeke; Deborah Okeke-Obayemi; Sanni Yaya (Discover Public Health)
Abstract Introduction Female Genital Mutilation/Cutting (FGM/C) has significant implications for reproductive health, including childbirth. Women who have undergone FGM/C are more likely to experience complications during delivery, such as obstructed labour, fistulas, and excessive bleeding. While there is evidence suggesting that FGM/C can lead to adverse obstetric outcomes, it is unclear whether FGM/C directly increases the likelihood of requiring a Caesarean section, particularly in sub-Saharan Africa. In this study, we aim to explore whether FGM/C decreases the likelihood of a C-section in singleton births across sub-Saharan Africa. Methods This is a cross-sectional study using Demographic and Health Survey data from Burkina Faso, Gambia, Kenya, Senegal, and Tanzania. The study targeted women aged 15–49 with a total sample of 28,176. Initially, bivariate analysis was conducted to assess the association between FGM/C and C-Section, as well as other covariates. A multivariable logistic regression model was then used to examine the association between FGM/C and the likelihood of C-Section, adjusting for potential confounders. The adjusted odds ratios (AOR) and 95% confidence intervals (CI) were calculated to determine the strength of association between FGM/C and C-Section, after controlling for other variables. Data analysis was performed using STATA™ software version 17. Results Our findings show that approximately 6800, 37.06% (95% CI 36.37, 37.76%) of women across the 5 sub-Saharan African countries reported they had undergone female genital mutilation. The data reveals that about 2280 (8.09%, 95% CI 7.78, 8.42%) women had singleton birth in the past 5 years through caesarean section. After controlling for potential confounders, it was found that women who had undergone FGM were 31% less likely to have Cesarean sections (AOR = 0.69, 95% CI 0.56, 0.84). On the other hand, there was higher likelihood of C-section rate among women at first birth 31–36 years (AOR = 1.83, 95% CI 1.07, 3.13). Higher birth weight (AOR = 1.69, 95% CI 1.13, 2.53), and higher education levels for both women (AOR = 1.61, 95% CI 1.23, 2.10) and their husbands (AOR = 1.75, 95% CI 1.34, 2.28) were associated with increased odds of Caesarean sections. Conclusion The study showed that about 2 in 5 women in the selected five sub-Saharan African countries had undergone FGM/C with a high level of between countries disparity in FGM/C prevalence. There was a relatively low prevalence of Caesarean section with variations based on age, education, and wealth. Based on the findings, policy and advocacy efforts should focus on prohibiting FGM/C and engaging community leaders to challenge harmful norms. Public awareness campaigns are essential to educate the public about the risks of FGM/C and the benefits of safe childbirth practices, like Caesarean sections.